The Influence of Customers Satisfaction, Switching Barrier and Trust for Brands on Customer Retention: A Research on Millennials - Agung Novianto Margarena; Zakky Fahma Auliya (UIN Raden Mas Said Surakarta, 2020)
The purpose of this research is to retest the relation between customer satisfaction, switching barrier, brand trust toward customer retention due to differences between the results from Ranaweera and Prabhu (2003); Dimyati (2015) and Marasabessy et al. (2014); Ullah et al. (2015). This research employed the sample of millennials who have been using IM3 for at least 6 months (coming from Surakarta with the number of 160 respondents) and were taken by the purposive sampling technique. This research used three variables namely dependent variable, independent variable and intervening variable. The employed research method would be the quantitative method. The employed data analysis tool is SEM AMOS version 21.0. The result of this research indicated that all the direct relations had a significant influence. Customer satisfaction and switching barrier affected the brand trust significantly. Customer satisfaction and switching barrier affected customer retention significantly. It was identified that the indirect relation between brand trust as an intervening variable and the customer satisfaction as well as switching barrier had no impact on customer retention.